2021
DOI: 10.3389/fcosc.2021.669563
|View full text |Cite
|
Sign up to set email alerts
|

Born to Be Wild: Evaluating the Zoo-Based Regent Honeyeater Breed for Release Program to Optimise Individual Success and Conservation Outcomes in the Wild

Abstract: Evaluating the effectiveness of captive breeding programs is central to improving conservation outcomes in released animals. However, few studies have assessed the impact of the strategies and trade-offs involved in husbandry decisions and the selection of traits on the success of breeding programs. This study evaluated a range of husbandry features including an animal's environment, health, and traits of the released individual and its parents involved in the zoo-based Regent Honeyeater breed for release prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Analytical approaches are available to contrast the potential outcomes of releasing different age classes (Robert et al ., 2004) and such approaches should be implemented alongside experimental releases that can inform underlying model assumptions. Other reasons that individuals may be unsuitable for release include biosecurity risks, inappropriate behaviours for life in the wild, or because some other phenotypic trait makes them less likely to thrive after release (Tripovich et al ., 2021). There is unlikely to be a ‘one size fits all’ rule for which individuals are most likely to achieve reintroduction aims.…”
Section: Reducing the Phenotypic Costs Of Captivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical approaches are available to contrast the potential outcomes of releasing different age classes (Robert et al ., 2004) and such approaches should be implemented alongside experimental releases that can inform underlying model assumptions. Other reasons that individuals may be unsuitable for release include biosecurity risks, inappropriate behaviours for life in the wild, or because some other phenotypic trait makes them less likely to thrive after release (Tripovich et al ., 2021). There is unlikely to be a ‘one size fits all’ rule for which individuals are most likely to achieve reintroduction aims.…”
Section: Reducing the Phenotypic Costs Of Captivitymentioning
confidence: 99%
“…Conservation practitioners should be prepared to attempt multiple, small‐scale ‘experimental’ releases to test a‐priori hypotheses with rigorous post‐release monitoring and refine bespoke strategies though adaptive management. Such attempts can reveal useful insights about how to improve reintroduction success (Tripovich et al ., 2021; Troy & Lawrence, 2021).…”
Section: Reducing the Phenotypic Costs Of Captivitymentioning
confidence: 99%
“…In zoos, there has been an overwhelming focus on environmental enrichment that recreates naturalistic-looking environments but is also motivated by giving aesthetic and educational value to visitors [10,[158][159][160]. From the published literature, it seems conservationfocused enrichment has a number of goals including increasing behavioural diversity and skill learning [143,[147][148][149]161]. A recent meta-analysis of 41 vertebrate translocations found that enrichment is associated with higher survival [162], but the authors did not identify which element(s) of enrichment are linked to survival success.…”
Section: Targeted Challengesmentioning
confidence: 99%
“…Wing shape strongly predicts flight efficiency (Lockwood et al, 1998; Sheard et al, 2020). Given that migratory birds are commonly bred in captivity for reintroduction (Burnside et al, 2017; Davis, 2010; Hutchins et al, 2018; Stojanovic, Potts, Troy, et al, 2020; Tripovich et al, 2021), quantifying the ubiquity of deleterious captive wing shape phenotypes and their post‐release fitness consequences is critical information.…”
Section: Introductionmentioning
confidence: 99%